Research Progress of Cam Tappet Laser Surface Modification and Friction Reduction and Wear Resistance - ZHANG Yipeng, CHEN Wengang, ZHANG Yao, YANG Xiaodong, XIE Hanchong, FENG Jinming (Cailiao Baohu, 2025)
Reducing friction loss is an important aspect of improving engine efficiency.The cam tappet mechanism， as an important component of the engine gas distribution mechanism， accounts for over 70%of frictional energy consumption in the engine gas distribution mechanism by friction.Therefore，investigating the tribological performance of cam tappet friction pairs is indispensable for ensuring optimal engine operational efficiency.Among various surface treatment technologies， laser surface treatment has been widely applied to improve the tribological properties of materials，demonstrating excellent performance in friction reduction and wear resistance.This paper reviewed recent advances in wear mechanisms of cam tappet friction pairs and summarized key factors influencing their tribological performance.The friction-reduction effect of the cam tappet friction pair was analyzed from three aspects: laser quenching， laser-cladded coating and laser surface texture， which could provide a reference for subsequent researchers in this direction.Finally， combining the existing research and future demands， the prospects for applying laser surface treatment technologies to friction-reduction studies of cam tappet systems were provided.